Effect of Transplanting on Yield and Growth of Grain Sorghum (Sorghum bicolor (L.) Moench) - Agbaje, GO.; Olofintoye, JA. (Tropicultura, 2002)
An experiment was carried out to study the effects of transplanting on growth and grain yield of three varieties of Sorghum bicolor, 'Ilorin local', SK 5912, and SSV10. Seedlings from each variety transplanted at 2, 4 and 6 weeks after planting (WAP) were compared with directly seeded plants used as control. Results show that at 8 WAP with seedlings transplanted at 2 WAP were taller than the other transplants, but shorter than directly seeded plants. Transplanting caused delay in flowering, but at this stage, height of transplants was comparable to directly seeded plants in SK 5912 and SSV10, while in 'Ilorin local' the transplants were significantly shorter at P< 0.05. Dry matter accumulation and grain yield was comparable among transplants but lower than those of directly seeded plants. However, grain yield of seedlings that were transplanted at 2 WAP was statistically comparable with directly seeded plants at P< 0.05.